2017
DOI: 10.1161/hypertensionaha.116.08154
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Progranulin in Hyperhomocysteinemia-Induced Cardiorenal Dysfunction

Abstract: for the therapeutic potential of PGRN in hHcys-induced cardiorenal dysfunction, which was associated with the negative regulation of Wnt/β-catenin signaling. Materials and MethodsAn extended Materials and Methods section can be found in the online-only Data Supplement. AnimalsTwelve-week-old male PGRN-deficient (Grn −/− ) mice and wild-type C57BL/6 mice were purchased from the Jackson laboratory (Bar Harbor, ME).Abstract-Hyperhomocysteinemia (hHcys) is an important independent risk factor for the development o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
1
13
1
Order By: Relevance
“…Our results may be therefore viewed as hypothesis generating and indicate a need for further studies. The equivocal role of progranulin is further illustrated by the fact that it exerted a stimulatory effect on insulin resistance, which goes in line with our observation on higher GRN levels in diabetic patients, but there is also evidence of its beneficial role in reducing renal and cardiac damage in animal models …”
Section: Discussionsupporting
confidence: 84%
“…Our results may be therefore viewed as hypothesis generating and indicate a need for further studies. The equivocal role of progranulin is further illustrated by the fact that it exerted a stimulatory effect on insulin resistance, which goes in line with our observation on higher GRN levels in diabetic patients, but there is also evidence of its beneficial role in reducing renal and cardiac damage in animal models …”
Section: Discussionsupporting
confidence: 84%
“…Moreover, administration of recombinant PGRN before LPS treatment in wild-type mice was associated with reduced renal injury [ 37 ]. Finally, in a mice model of hyperhomocysteinemia (a risk factor for kidney disease), PGRN-deficient mice also presented exacerbated renal injury, that could be ameliorated by pretreatment with recombinant human PGRN [ 38 ]. In this context, PGRN could be a renal protective molecule in an inflammatory environment.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, we found that TIPE1 negatively regulated Wnt signalling which is an evolutionarily conserved developmental signalling cascade that exhibits a pivotal function in regulating a variety of biologic processes . The canonical Wnt pathway is also known as the Wnt/β‐catenin pathway as β‐catenin is a key transducer of the Wnt signal from the cytoplasm to the nucleus.…”
Section: Discussionmentioning
confidence: 99%